1986
DOI: 10.1111/j.1467-1770.1986.tb00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity Tolerance and Field Independence as Predictors of Proficiency in English as a Second Language

Abstract: The fact that some adults are more successful at acquiring an L2 than others has led to investigations of individual characteristics as predictors of successful L2 acquisition. This paper reports the results ofan investigation of the relationship between two learner characteristics, Ambiguity Tolerance (AT) and Field Independence (FI), and adult learners' acquisition of English as a Second Language in the United States. A Multiple Regression Analysis revealed that AT and F1 accounted for a significant amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0
2

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(112 citation statements)
references
References 24 publications
5
105
0
2
Order By: Relevance
“…Chapelle and Roberts (1986) found a significant correlation between field independence andcloze test performance in ESL students. In a similar study, Hansen and Stansfield (1981) found a positive relationship between field independence and scores on L2 tests, particularly in the case of the cloze tests.…”
Section: Cloze Test Performancementioning
confidence: 93%
“…Chapelle and Roberts (1986) found a significant correlation between field independence andcloze test performance in ESL students. In a similar study, Hansen and Stansfield (1981) found a positive relationship between field independence and scores on L2 tests, particularly in the case of the cloze tests.…”
Section: Cloze Test Performancementioning
confidence: 93%
“…Another important related study is the one made by Chapelle & Roberts (1986). Employing Norton's MAT-50 (1975), a 61-item Likert type scale, as the measurement of tolerance of ambiguity, they put this scale into practical research for the first time.…”
Section: A Researches Overseamentioning
confidence: 99%
“…Some studies of ambiguity tolerance deal with the relationship between AT and ethnocentrism or authoritarianism (O'Conner, 1952;Levitt, 1953;Budner, 1962;Ehrlich, 1965;Chapelle, 1983); some refer to AT and learners' rigidity or receptivity of change (MacDonald, 1970;McLain, 1993); some mention about AT and other variables, such as Field Dependence/ Independence (Chapelle & Roberts, 1986), or strategy use (Ely, 1989); some focuse on AT and second/foreign language success (Pimsleur et al, 1966;Naiman, 1975;MacDonald,1970;Chapelle, 1983;Chapelle & Roberts, 1986;Chapelle & Jamison, 1986;Ely, 1986, Chen, 1989. Subjects of many studies are university students, with an exception in Levitt's (1953), in which subjects are elementary school students, and in Naiman et al's (1975), in which subjects are high school students.…”
Section: Tolerance Of Ambiguitymentioning
confidence: 99%
“…They prefer memory or strategies which involve focusing on individual language elements (Ely, 1989), are more rigid (MacDonald,1970) and less inclined to take risks (Ely, 1995). They are easy to resort to black-and-white solutions (Frenkel-Brunswik,1949), have the tendencies to avoid ambiguous situations (Chapelle & Roberts, 1986), or even drop the subject (Naiman, et al,1975). On the contrary, people with more tolerance of ambiguity appreciate being in ambiguous situations.…”
Section: Tolerance Of Ambiguitymentioning
confidence: 99%